Aplikasi Pembelajaran Pengenalan Hewan dan Buah-Buahan Menggunakan Bahasa Jepang dan Inggris Berbasis Android - Abd. Basith (Journal on Education, 2023)
The rapid development of technology, especially computers, has an impact in the world of education in utilizing computers. Computers can be used as one of the interactive learning media. To make it easier to deliver learning materials to children, this material is attractively packaged in the form of multimedia that is educational and entertaining. Learning media is a tool or technique used in the teaching and learning process so that the teaching and learning process becomes more interesting and the material conveyed can reach students precisely and quickly. Based on this definition, it can be concluded that learning media has great benefits in the teaching and learning process. The learning media used must be interesting so that students can pay more attention to the material conveyed in the teaching and learning process. Based on the above problems, an introduction learning media application using multimedia-based English was made which can be used as an alternative to the problems above, therefore in this study the title Learning Media Application Using Japanese and English Through Introduction to Animals, Fruits, Multimedia-Based was taken.